Outcomes of patients with drug-resistant-tuberculosis treated with bedaquiline-containing regimens and undergoing adjunctive surgery. Issue 1 (January 2019) - Borisov, Sergey E.; D'Ambrosio, Lia; Centis, Rosella; Tiberi, Simon; Dheda, Keertan; Alffenaar, Jan-Willem; Amale, Rohit; Belilowski, Evgeny; Bruchfeld, Judith; Canneto, Barbara; Denholm, Justin; Duarte, Raquel; et al.
Highlights: Treating MDR-TB is complicated, long and expensive. Bedaquiline (BQ) is a new active drug to treat MDR-TB. No study evaluated safety and effectiveness of surgery in BQ-treated patients. 57 BQ-exposed cases resistant to 7 drugs (median) underwent surgery in 9 countries. 60% of cases initiated BQ after surgery, 36.4% before and completed it afterwards. 90% culture-converted and 69.1% achieved treatment success at the end of treatment. Summary: Objectives: No study evaluated the contribution of adjunctive surgery in bedaquiline-treated patients. This study describes treatment outcomes and complications in a cohort of drug-resistant pulmonary tuberculosis (TB) cases treated with bedaquiline-containing regimens undergoing surgery. Methods: This retrospective observational study recruited patients treated for TB in 12 centres in 9 countries between January 2007 and March 2015. Patients who had surgical indications in a bedaquiline-treated programme-based cohort were selected and surgery-related information was collected. Patient characteristics and surgical indications were described together with type of operation, surgical complications, bacteriological conversion rates, and treatment outcomes. Treatment outcomes were evaluated according to the time of surgery. Results: 57 bedaquiline-exposed cases resistant to a median of 7 drugs had indication for surgery (52 retreatments; 50 extensively drug-resistant (XDR) or pre XDR-TB). Sixty percent of cases initiated bedaquiline treatment following surgery, while 36.4% underwent the bedaquiline regimen before surgery and completed it after the operation. At treatment completion 90% culture-converted with 69.1% achieving treatment success; 21.8% had unfavourable outcomes (20.0% treatment failure, 1.8% lost to follow-up), and 9.1% were still undergoing treatment. Conclusions: The study results suggest that bedaquiline and surgery can be safely and effectively combined in selected cases with a specific indication.